Assessment of right ventricular fibrosis in different forms of pulmonary atresia with ventricular septal defect - van de Woestijne, Pieter C (Pulsus Group Inc, 2004)
BACKGROUND: In pulmonary atresia with ventricular septal defect (PA-VSD), the corrective surgical strategy aims to reduce the right ventricular (RV) overload and restore physiological pulmonary perfusion before the characteristic RV hypertrophy and fibrosis become irreversible. OBJECTIVE: To assess RV fibrosis in different forms of PA-VSD. METHODS: RV biopsies were obtained at corrective surgery from PA-VSD patients (n=14, mean age 2.5±1.2 years) with patent arterial duct (PAD group, n=6; mean age 1.7±0.5 years) or systemic-pulmonary collateral arteries (SPCA group, n=8; mean age 3.2±1.2 years) and from age-matched controls (control group, n=6; mean age 2.5±1.8 years). Myocardial expression patterns (messenger RNA [mRNA] and protein levels) of the extracellular matrix proteins (eg, fibronectin and collagens [subtype I alpha and III) were quantitatively analyzed in relation to myocardial cell hypertrophy. RESULTS: Comparing the age of PA-VSD patients at surgery, the SPCA group was older than the PAD group (P=0.01). Expression analysis by reverse transcriptase polymerase chain reaction showed significantly higher mRNA levels in patients with PA-VSD for collagen III (PA-VSD versus controls; 0.9±0.2 versus 0.6±0.1, P=0.03) than in controls, whereas collagen I alpha and fibronectin mRNA levels did not differ. No differences were found between the PAD and SPCA groups. The myocyte cross sectional surface area showed enhanced myocyte hypertrophy in patients with PA-VSD compared with the control group (P=0.015), with no significant difference between the PAD and SPCA groups. Video image analysis of immunohistochemical staining corrected for hypertrophy revealed unchanged interstitial collagens and fibronectin levels in all groups. However, perivascular staining corrected for the vessel lumen area showed significantly lower total collagen levels in patients with PA-VSD than in the control group (3.2±1.2 versus 7.2±2.8, respectively; P=0.004). CONCLUSIONS: The results indicate that the extracellular matrix support for the coronary blood vessels appears to be suboptimal in patients with PA-VSD. The staged surgical approach in the SPCA group (with a higher age at correction) did not result in an excessive accumulation of fibrosis markers in the RV myocardium.